Caracterização microestrutural e mecânica da liga de Al AA7050 reciclada por conformação por spray e extrusão - Mazzer, Eric Marchezini (2013)
Aluminium alloys of the 7000 series are widely used in structural components in the aircraft industries due to their high strength and low density. However, a large amount of scraps is generated by the machining of the components, which achieves almost 90% of the alloy s initial mass. These wastes are normally used in low performance application, despite of the high quality of the AA7050 alloys. It occurs because is not possible to keep the good mechanical properties of the alloy when it is recycled by conventional casting, which generates high level of segregation of the alloy elements and a coarse microstructure. In this sense, the present work aims the recycling of the aluminium scraps by spray forming and hot extrusion. The spray forming process provides a rapid solidification, making possible to obtain a refined microstructure and a low level of segregation. The hot extrusion closes the pores arising from the previous process and increases the strength by reducing the grain size. After the spray forming the material was hot extruded in a industrial scale equipment in order to close the pores arising from the previous process and improve the strength. A combination of heat treatments concerning homogenization, solution and aging heat treatments were imposed during the process in order to optimize the mechanical properties. The microstructure characterization was carried out in a scanning electronic microscope (SEM) and in a transmission electronic microscope (TEM), combined with x-ray diffraction (XRD) and differential scanning calorimetry (DSC) . The mechanical properties were evaluated by tensile tests. By the analysis of the results we can conclude that the spray forming is a viable route to recycle the Al AA7050 alloys because it can generate refined microstructure and better mechanical properties than the original material.